El retiro sin consentimiento del preservativo durante las relaciones sexuales. Análisis desde la teoría del delito y el derecho comparado - Velásquez Baho, Evelin Salomé (2024)
The present curricular integration work entitled: “The removal without consent of the condom during sexual relations. Analysis from the theory of crime and comparative law", has the general objective of carrying out a legal and doctrinal study on this conduct, known in English as 'stealthing', from the theory of crime and comparative law, to understand this phenomenon and recommend state actions within the framework of the national and international obligations of the Ecuadorian State. This study adopted a multidimensional methodology that included scientific, analytical, inductive, deductive, comparative, statistical and life story methods, along with surveys of 30 lawyers specialized in criminal law and interviews with experts in criminal law and gender violence. The research is based on a detailed analysis of the legislation in countries such as Spain, Costa Rica, Chile and Singapore. In addition, an exhaustive analysis of national and international legislation was carried out, including the Constitution of Ecuador and international treaties such as the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) and the Convention on the Elimination of All Forms of Discrimination against Women “Convention of Belém do Pará”. Through the theory of crime, the objective typicality of "stealthing" in Spanish legislation was analyzed, concluding that the consent given to maintain sexual intercourse implies the condition of using a condom; withdrawing it without prior agreement violates this initial consent. The results reveal that, unlike other countries where this behavior is classified, in Ecuador there is no classification in the Penal Code (COIP), a situation that is problematic given that this practice perpetuated mainly by men against women, is a form of of sexual violence often motivated by gender rules and violates legal rights protected in the Constitution, such as sexual integrity and sexual freedom, which highlights the need for the Ecuadorian State to include this conduct in the criminal legal framework, complying with the obligations established by international human rights instruments, and develop affirmative action and awareness programs on sexual consent.